Evaluation of anti-diabetic activity of etlingera elatior flower (bunga kantan) aqueous extract in rat with type 2 diabetes mellitus induced by high-fat diet and streptozotocin - Nor, Nor Asiah Muhamad (2022)
Diabetes mellitus (DM) is a global public health concern that leads to multiple complications, including renal failure. Nowadays, the use of medicinal plants in disease management is increasing exponentially due to their beneficial health effects. Traditionally, the flower of Etlingera elatior (bunga kantan) has been used as a supplement for diabetic management. However, very little scientific evidence on the efficacy of this plant in DM. This study aims to determine the anti-diabetic effect of E. elatior flower aqueous extract (EEAE) and improvement in renal damage on the type 2 DM rat (T2DR) model. The in vitro antioxidant, and in vitro anti-diabetic activity of EEAE were determined by inhibition of carbohydrate digestive enzymes. The T2DR model was achieved using a combination of high-fat diet (HFD) feeding and streptozotocin (STZ). Forty-nine male Sprague-Dawley (SD) rats were equally divided into seven groups; normal, obese, untreated-DM, metformin-treated, and EEAE-treated at 500, 1000, and 2000 mg/kg. All treatments were orally administered for 6 weeks. The fasting blood glucose (FBG) and body weight were measured weekly, while the systolic blood pressure (SBP) was fortnightly. At the end of the study, levels of biochemical parameters and antioxidant biomarkers were determined. The histology of the liver, kidney, pancreas, and aorta was assessed using haematoxylin and eosin (H&E) stain. The kidney tissue was further evaluated by scanning electron microscopy (SEM) analysis and special staining; periodic acid Schiff (PAS) and Masson’s trichrome (MT). Furthermore, the levels of interleukin-6 (IL-6), transforming growth factor-beta (TGF-β), and connective tissue growth factor (CTGF) in kidney tissue were elucidated. There were significant in vitro antioxidant activities, and in vitro inhibition on α-amylase and α-glucosidase enzymes. In EEAEtreated T2DR, FBG and SBP were significantly lower compared to other groups. When compared to untreated-T2DR, EEAE improved lipid profile, renal and liver function tests, and significantly increased antioxidant biomarkers levels (superoxide dismutase/SOD, catalase/CAT, and glutathione/GSH). In addition, there was an improvement in liver, kidney, and pancreatic histology of EEAE-treated at low and medium doses. EEAE also decreased the level of IL-6, TGF-β, and CTGF in kidney tissue. In conclusion, E. elatior has anti-diabetic activity, which can be attributed to its antioxidant properties and reduction of the inflammatory process.